2017
DOI: 10.1063/1.4979846
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ordered islands on surface resistivity: Ni on Au(111)

Abstract: The change in surface resistivity due to the formation of nickel islands on gold(111) was studied by measuring the resistance of a thin film of Au as a function of Ni coverage, θ. Previous studies showed that the Au(111) herringbone reconstruction provides a template for the periodic growth of ordered islands. Ni islands grow radially until θ ≈ 0.3 ML, after which subsequent Ni atoms contribute primarily to a second layer. Since Ni atoms on Au(111) grow in ordered nanoclusters, a nonlinear dependence of resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 51 publications
4
10
0
Order By: Relevance
“…In our study of Ni islands, we found ρ s to increase linearly with the Ni coverage θ Ni , until a transition coverage, above which additional Ni atoms contributed very little to surface resistivity. 26 The transition point where ρ s plateaued corresponded closely with the transition point (approximately 0.3 ML) where second layer Ni begins forming, according to STM studies. We concluded that Ni atoms in the first layer contribute evenly to ρ s , while second layer Ni makes little to no contribution to ρ s .…”
Section: Introductionsupporting
confidence: 61%
See 4 more Smart Citations
“…In our study of Ni islands, we found ρ s to increase linearly with the Ni coverage θ Ni , until a transition coverage, above which additional Ni atoms contributed very little to surface resistivity. 26 The transition point where ρ s plateaued corresponded closely with the transition point (approximately 0.3 ML) where second layer Ni begins forming, according to STM studies. We concluded that Ni atoms in the first layer contribute evenly to ρ s , while second layer Ni makes little to no contribution to ρ s .…”
Section: Introductionsupporting
confidence: 61%
“…The Ni island on Au(111) systems has been of interest in a variety of studies. 13,[21][22][23][24][25][26] When cleaned and annealed, the Au(111) surface configures into the herringbone reconstruction, [27][28][29] shown schematically in Fig. 1(a) and described in more detail in Ref.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations